On the Move to Meaningful Internet Systems: OTM 2011 Confederated International Conferences: CoopIS, DOA-SVI, and ODBASE 2011, Hersonissos, Crete, Greece, October 17-21, 2011, Proceedings, Part II - Meersman, Robert; Dillon, Tharam; Herrero, Pilar; Kumar, Akhil; Reichert, Manfred; Qing, Li.; Ooi, Beng-Chin.; Damiani, Ernesto; Schmidt, Douglas C.; White, Jules; Hauswirth, Manfred; Hitzler, Pascal; et al. (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
The two-volume set LNCS 7044 and 7045 constitutes the refereed proceedings of three confederated international conferences: Cooperative Information Systems (CoopIS 2011), Distributed Objects and Applications - Secure Virtual Infrastructures (DOA-SVI 2011), and Ontologies, DataBases and Applications of SEmantics (ODBASE 2011) held as part of OTM 2011 in October 2011 in Hersonissos on the island of Crete, Greece. The 55 revised full papers presented were carefully reviewed and selected from a total of 141 submissions. The 28 papers included in the second volume constitute the proceedings of DOA-SVI 2011 with 15 full papers organized in topical sections on performance measurement and optimization, instrumentation, monitoring, and provisioning, quality of service, security and privacy, and models and methods, and ODBASE 2011 with 9 full papers organized in topical sections on acquisition of semantic information, use of semantic information, and reuse of semantic information and 4 short papers.
Keywords: Computer science; Computer Communication Networks; Software engineering; Computer software; Artificial intelligence; Information Systems; Computer Science; Computer Communication Networks; Software Engineering; Information Systems Applications (incl. Internet).; Artificial Intelligence (incl. Robotics).; Algorithm Analysis and Problem Complexity; Management of Computing and Information Systems